The coach's role during an athlete's rehabilitation following sports injury: A scoping review. Issue 3 (June 2023) - King, Jamie; Burgess, Theresa L; Hendricks, Candice; Carson, Fraser
Coaches play a pivotal role during an athletes' rehabilitation, assisting them to deal with the psychological challenges linked with injury recovery and return to sport. However, coaches' views of their roles during rehabilitation, and the extent to which their influences may facilitate psychological coping is unclear. Although athletes value input from their coaches during their injury rehabilitation, their satisfaction with the support provided is varied. To explore the current literature on the role of coaches during an athlete's rehabilitation from injury, a scoping review, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews guidelines, was conducted on EBSCOhost, PubMed and Scopus databases. A total of 27 articles met the inclusion criteria after 2716 studies were excluded based on the eligibility criteria during phases of title, abstract and full-text screening. Factors to consider when exploring coaches' roles during injury rehabilitation include athlete's and coaches' age and gender, the type of sport and level of competition, the athletes' role in the team, and the injury severity and type. The major role that coaches play during rehabilitation is providing social support to the injured athlete. The amount and availability of social support, as well as different forms of social support and their perceived prominence to athletes' well-being, are key concepts worth considering when analyzing the role of coaches during injury rehabilitation. Social support provided by coaches to athletes undergoing rehabilitation aids in maintaining the coach–athlete relationship, thereby preventing any unrest between the two upon return to sport.